2019
DOI: 10.1097/gox.0000000000002436
|View full text |Cite
|
Sign up to set email alerts
|

Flow-through Omental Flap for Vascularized Lymph Node Transfer: A Novel Surgical Approach for Delayed Lymphatic Reconstruction

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 10 publications
1
18
0
Order By: Relevance
“…By decreasing flap inflow and increasing flap outflow, the omental flow-through approach resolves this issue. 3 In this case, we used the flowthrough method and discovered no postoperative venous hypertension or stealing effect. However, during the arterial phase of the postoperative CT scan, an early enhancement of the omental and limb venous system was observed.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…By decreasing flap inflow and increasing flap outflow, the omental flow-through approach resolves this issue. 3 In this case, we used the flowthrough method and discovered no postoperative venous hypertension or stealing effect. However, during the arterial phase of the postoperative CT scan, an early enhancement of the omental and limb venous system was observed.…”
Section: Discussionmentioning
confidence: 74%
“…2 Venous congestion is a common complication after omental flap microvascular anastomosis. 3 The flowthrough configuration in the omental flap creates a natural vasculature flow and reduced venous congestion. 4 The purpose of this study was to demonstrate our experience in total omental flow-through flap in lower extremity lymphedema.…”
mentioning
confidence: 99%
“…Five studies utilized gastroepiploic VLNTs, and of those only one mentioned supercharging. 16 The wrist was the recipient site of choice in 48.0% ( n = 331/689) and the axilla in 52.0% ( n = 358/689) of patients included. Among included patients, the overall weighted CRR was 46.7% (range: 24.9–58.7), with an average follow-up of 38.0 months, and the overall weighted EVR was 46.2% (19.3–58.8), with an average follow-up of 27.4 months.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies reported using the wrist as a recipient site for VLNT, totaling 331 patients. 9 12 16 17 18 19 20 21 22 23 24 25 26 27 The mean age of patients was 54.2 years (range: 48.0–57.5) and the mean BMI was 27.6 kg/m 2 (range: 25.9–32.6). On average, the mean time from diagnosis of BCRL to VLNT treatment was 2.08 years (range: 1.6–12.1) and 81.6% ( n = 177/217) received adjuvant radiotherapy to either the lymph node basin or breasts.…”
Section: Resultsmentioning
confidence: 99%
“…8 In the upper extremity, we proposed a novel inset with a second arterial and venous anastomosis, thereby recreating the omentum’s natural flowthrough physiology. 5 In this case series, we describe our lower extremity approach to omental vascularized lymph node transplantation with a middle leg recipient site and flowthrough configuration.…”
mentioning
confidence: 99%